Black thunder : an Ella Clah novel - Thurlo, Aimée (Thurlo, Aimée. Ella Clah novels., 2011)
"A construction crew found the first body. The cops found three more, in a cluster that lay on both sides of the border of the Navajo Reservation. Because some of the bodies were buried outside the Rez, Navajo Police Special Investigator Ella Clah and her team must work a delicate joint investigation with the New Mexico police. Identifying the dead isn't easy--some had been buried for years--and at first the cases look to be nothing but dead ends. Then one of the bodies turns out to be that of a missing man who was believed to have embezzled funds from his construction firm and suspicions focus on the man's partner. With no obvious links between any of the corpses and the anniversary of their deaths fast approaching, Ella feels frustrated by the investigation's lack of progress. Unless they can find what connects these victims, someone else may soon be killed. Ella's ability to concentrate is battered by worries about her teenage daughter, who has been skipping school, and her mother, who is cooking up a storm, a sure sign that trouble is brewing in the household. Black Thunder, an Ella Clah novel, is a police procedural mystery that should appeal to all readers. "--